Rivaroxaban versus warfarin for the management of left ventricle thrombus - Albabtain, Monirah A. (Egypt Heart J, 2021)
BACKGROUND: Rivaroxaban has been recently introduced for the management of non-valvular intra-cardiac thrombosis with variable results. We aimed to compare the results of the off-label use of rivaroxaban versus warfarin in the management of patients with left ventricle (LV) thrombus. This research is a retrospective study conducted on 63 patients who had LV thrombus from January to December 2016. We compared patients treated with warfarin (n=35) to patients who had rivaroxaban (n=28), and study outcomes were time to thrombus resolution, bleeding, stroke, and mortality. RESULTS: The median duration of treatment was 9.5 (25th-75th percentiles: 6-32.5) months for rivaroxaban and 14 (3-41) months for warfarin. Thrombus resolution occurred in 24 patients in the warfarin group (68.6%) and 20 patients in the rivaroxaban group (71.4%). The median time to resolution in the warfarin group was 9 (4-20) months and 3 (2-11.5) months in the rivaroxaban group. Thrombus resolution was significantly faster in patients on rivaroxaban (p= 0.019). Predictors of thrombus resolution were thrombus surface area (HR: 1.21; CI 95% (1.0-1.46); p= .048) and the use of rivaroxaban (HR: 1.92; CI 95% (1.01-3.65); p= 0.048). There was no difference in stroke, bleeding, and mortality between both groups. CONCLUSION: Rivaroxaban was as effective and safe as warfarin in managing patients with left ventricle thrombus. Larger randomized clinical trials are recommended to confirm our findings.